Improving Pronunciation Ability and Teaching Pronunciation for Student Through Listening English Song - Ana Widiyanti (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2019)
This article aims to know the pronunciation teaching process through an English song. Also to know the difficultness which students feel. Pronunciation is important for a student because to know what the meaning of the song we must pronoun the right word, as far as I know, what te different pronoun had different meanings whereas the word is the same. This article uses qualitative methods to take some samples in the first semester students of the English education program. Some sample pronoun some words that on the song what I choose the song "a whole new world" and "diamond". The students can receive what the teacher teaches. Whereas some of them get trouble but they learn so enthusiasm. The students find difficulties in pronouncing the words containing fricatives consonants. Fricatives consonants are consonants that are made when we squeeze air through a small hole or gap into our mouth.